A majorization–minimization-based method for nonconvex inverse rig problems in facial animation - Racković, Stevo (2024)
This work has received funding from the European Union’s Horizon 2020 research and innovation program under the Marie Skłodowska-Curie grant agreement No. 812912, from FCT IP strategic project NOVA LINCS (FCT UIDB/04516/2020) and project DSAIPA/AI/0087/2018. The work has also been supported in part by the Ministry of Education, Science and Technological Development of the Republic of Serbia (Grant No. 451-03-9/2021-14/200125) and Provincial Secretariat for Higher Education and Scientific Research (Grant No. 142-451-2593/2021-01/2). Funding Open access funding provided by FCT|FCCN (b-on). Publisher Copyright: © 2023, The Author(s).